2021
DOI: 10.1039/d0nr08741f
|View full text |Cite
|
Sign up to set email alerts
|

Molecular self-assembly of a tyroservatide-derived octapeptide and hydroxycamptothecin for enhanced therapeutic efficacy

Abstract: Tyroservatide (YSV) belongs to a class of bioactive peptides that have drawn considerable attention in the field of drug discovery, yet it displays limited potency and often requires a millimolar...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“… 155–158 Liu et al synthesized a novel octapeptide (1-YSV) to enable its co-assembly with HCPT to obtain supramolecular hydrogels with excellent viscoelasticity and increased the water stability of HCPT ( Figure 4 ). 159 Guo et al prepared a supramolecular hydrogel composed of a self-assembling peptide, HCPT and macrocyclic polyamine cyclen can depleting cellular ATP and reversing ATP-dependent drug efflux, greatly improving cellular uptake and nuclear aggregation of HCPT. 160
Figure 4 ( A ) Schematic illustration of co-assembly of tyroservatide-derived octapeptide (1-YSV) and HCPT for cancer therapy; ( B ) TEM micrograph of the 1-YSV hydrogel; and ( C ) TEM micrograph of the 1-YSV/HCPT hydrogel.
…”
Section: Organic Npsmentioning
confidence: 99%
See 1 more Smart Citation
“… 155–158 Liu et al synthesized a novel octapeptide (1-YSV) to enable its co-assembly with HCPT to obtain supramolecular hydrogels with excellent viscoelasticity and increased the water stability of HCPT ( Figure 4 ). 159 Guo et al prepared a supramolecular hydrogel composed of a self-assembling peptide, HCPT and macrocyclic polyamine cyclen can depleting cellular ATP and reversing ATP-dependent drug efflux, greatly improving cellular uptake and nuclear aggregation of HCPT. 160
Figure 4 ( A ) Schematic illustration of co-assembly of tyroservatide-derived octapeptide (1-YSV) and HCPT for cancer therapy; ( B ) TEM micrograph of the 1-YSV hydrogel; and ( C ) TEM micrograph of the 1-YSV/HCPT hydrogel.
…”
Section: Organic Npsmentioning
confidence: 99%
“…[155][156][157][158] Liu et al synthesized a novel octapeptide (1-YSV) to enable its co-assembly with HCPT to obtain supramolecular hydrogels with excellent viscoelasticity and increased the water stability of HCPT (Figure 4). 159 Guo et al prepared a supramolecular hydrogel composed of a self-assembling peptide, HCPT and macrocyclic polyamine cyclen can depleting cellular ATP and reversing ATP-dependent drug efflux, greatly improving cellular uptake and nuclear aggregation of HCPT.…”
Section: Hydrogel-based Npsmentioning
confidence: 99%
“…For example, a peptide-sequence screening for hydrogelation yielded the octapeptide FKFEYYSV, composed of the bioactive tripeptide YSV and the gelation moiety FKFEY which also increased the anticancer activity of YSV. In addition, hydroxycamptothecin was loaded on the hydrogel for simultaneous drug delivery, and the whole system showed good anticancer activity, without toxicity for non-cancerous cells [85]. A similar combined approach was developed using an EYSV peptide linked to taxol (taxol-EYSV) [86].…”
Section: Ysvmentioning
confidence: 99%
“…This significantly improved photothermal effect is attributed to the abundant oxygen vacancies on the surface of the ultrathin MnO 2 nanosheets, which was confirmed by the extended X‐ray absorption fine structure (EXAFS) data and density functional theory (DFT) calculation. Recently, Liu et al [ 162 ] reported that the enzymatically synthesized MnO 2 nanoparticles (Bio‐MnO 2 NPs) had extremely high photothermal conversion efficiency (44%) and showed excellent thermal cycle stability and solubility. This nanoparticle is prepared through an enzyme‐mediated biomineralization process, and the hexagonal layer symmetry of Bio‐MnO 2 NPs is a key feature to achieve the high photothermal conversion efficiency, which may be due to the abundant cation vacancies and rich oxygen permeation.…”
Section: Cancer Treatmentmentioning
confidence: 99%